2008 IEEE/RSJ International Conference on Intelligent Robots and Systems 2008
DOI: 10.1109/iros.2008.4650837
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of deformable environment with haptic feedback on GPU

Abstract: Interactive simulations of deformable bodies are a growing research area with possible applications in several fields, i.e. computer aided surgery. The main implementation issue is to mimic the real behavior of the body at the extremely high rates required by haptic devices. Since even high-end computers have inadequate performance, one possible solution is to exploit the parallelism of modern Graphics Processing Units.In this paper we present our research aiming at moving the whole computational process from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Another study presented a GPU-based approach to detect collision of items of 14.4 k, 2 k, and 1.7 k triangles with a processing rate of 153 Hz, which cannot meet the medical specification of 1 kHz (Mainzer and Zachmann, 2015). Nevertheless, Altomonte et al (2008) demonstrated the realization of a surgical simulation with haptic feedback at over 1 kHz rate, under a very high resolution. To achieve the comparable resolution, the previously mentioned FPGA cascading method has to be investigated and applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study presented a GPU-based approach to detect collision of items of 14.4 k, 2 k, and 1.7 k triangles with a processing rate of 153 Hz, which cannot meet the medical specification of 1 kHz (Mainzer and Zachmann, 2015). Nevertheless, Altomonte et al (2008) demonstrated the realization of a surgical simulation with haptic feedback at over 1 kHz rate, under a very high resolution. To achieve the comparable resolution, the previously mentioned FPGA cascading method has to be investigated and applied.…”
Section: Discussionmentioning
confidence: 99%
“…The OBB is also a cuboid, but flexibly oriented in 3D. Altomonte et al (2008) also demonstrates a full force feedback chain in an anatomical environment with a good performance.…”
mentioning
confidence: 93%
“…The presented simulator is based and extends the work proposed in [1] to which the reader is referred. Each simulation step is composed by three phases: collision detection and solution, internal force computation, temporal integration of model configuration.…”
Section: Soft Tissue Modellingmentioning
confidence: 96%
“…A different approach leads to MSMs [37] which have been widely used in surgical simulations [1,33]. In MSMs the body is discretized in a cloud of mass points linked by springs and dampers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation